ABDULLA ORIPOVNING "ESLASH" SHE’RI TAHLILI (Modern education and development, 2025)
She’riyat inson tafakkuri, hissiy kechinmalari va hayotiy tajribalarini aks ettirishning eng kuchli vositalaridan biridir. "Eslash" she’ri inson hayotidagi xavf-xatarlar, sinovlar va ularni yengib o‘tish falsafasi haqida bo‘lib, u hayotning murakkab yo‘llarini tasvirlaydi. Ushbu maqolada she’rning poetik va falsafiy xususiyatlarini ilmiy jihatdan tahlil qilamiz.Poetry is one of the most powerful means of reflecting human thinking, emotional experiences and life experiences. The poem "Remembering" is about the dangers and trials in human life and the philosophy of overcoming them, and it describes the complex ways of life. In this article, we will scientifically analyze the poetic and philosophical features of the poem.